Local corner smoothing transition algorithm based on double cubic nurbs for five-axis linear tool path - Zhang, Liqiang (Strojniški vestnik, 2016)
A five-axis tool path is often composed of a linear path that has a tangential discontinuity so that the tangential velocity will be abrupt or be equal to zero at the corner of the adjacent segments. Therefore, it greatly affects the machining efficiency and quality. Thus, a corner smoothing transition algorithm based on double cubic NURBS, which is curvature-continuous and satisfies the given accuracy constraint, is proposed to smooth the local corner at the adjacent five-axis linear path. On the basis of the smoothing transition model, the parametric synchronization between the smoothed double NURBS trajectories and the remaining two linear segments are respectively constructed to realize the smoothing variation along the tool tip translational trajectory and tool axis rotational trajectory. The simulation and examples show that the proposed transition algorithm can satisfy the error constraints, reduce the feedrate fluctuation, and improve the machining quality.
Keywords: dvojne krivulje NURBS; petosna obdelava; pot orodja; prehod v ogliščih